Konstruksi Realitas Feminisme dalam Film Barbie (Analisis Semiotika Charles Sanders Peirce) - Wiryana, Febiola; Azeharie, Suzy (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
This study aims to determine the process of communication accommodation by students in establishing friendship relationships. This research is motivated by the difficulty that Barbie is the first live-action film resulting from the adaptation of the legendary doll character of the Mattel company produced by Warner Bros and directed by Greta Gerwig. The movie tells the life story of Barbie and her adventures in the real world. Barbie is more than just a doll. It represents fashion trends and female beauty. Barbie symbolizes strength, diversity, and breaking stereotypes. The Barbie movie inserts several social ideologies, such as feminism and patriarchy. This research aims to describe the meaning and construction of the reality of feminism in the Barbie movie through the concepts of mass communication, reality construction, and feminism. This research uses Charles Sanders Peirce's semiotic analysis method, which is based on three main components: sign, object, and interpretant. The research found that there is a form of feminism that is built, gender discrimination against women depicted through scenes in the Barbie movie. The issue of feminism constructed in this movie does not disappear if the patriarchal system still dominates women. Feminism is an issue that continues to be fought for by feminist groups in developed and developing countries such as Indonesia. Barbie merupakan film aksi langsung pertama hasil dari adaptasi karakter boneka legendaris perusahaan Mattel yang diproduksi oleh Warner Bros dan disutradarai oleh Greta Gerwig. Film ini menceritakan kisah hidup para Barbie dan petualangannya di dunia nyata. Barbie lebih dari sekadar sebuah boneka yang merepresentasikan tren mode dan kecantikan perempuan. Barbie melambangkan kekuatan, keberagaman, dan mematahkan stereotip. Film Barbie menyisipkan ideologi sosial seperti feminisme dan patriarki. Penelitian ini menggambarkan makna dan konstruksi realitas feminisme dalam film Barbie melalui konsep komunikasi massa, konstruksi realitas, feminisme. Metode analisis semiotika Charles Sanders Peirce digunakan dengan tiga komponen utama yaitu tanda, objek, dan interpretan. Penelitian menemukan bentuk-bentuk feminisme yang dibangun, diskriminasi gender terhadap perempuan yang digambarkan melalui adegan-adegan dalam film Barbie. Isu feminisme yang dikonstruksi dalam film ini tidak hilang apabila sistem patriarki masih mendominasi perempuan. Feminisme menjadi isu yang terus diperjuangkan oleh kelompok feminis di negara maju maupun negara berkembang seperti Indonesia.